2018
DOI: 10.1111/rec.12869
|View full text |Cite
|
Sign up to set email alerts
|

Low‐tech riparian and wet meadow restoration increases vegetation productivity and resilience across semiarid rangelands

Abstract: Restoration of riparian and wet meadow ecosystems in semiarid rangelands of the western United States is a high priority given their ecological and hydrological importance in the region. However, traditional restoration approaches are often intensive and costly, limiting the extent over which they can be applied. Practitioners are increasingly trying new restoration techniques that are more cost-effective, less intensive, and can more practically scale up to the scope of degradation. Unfortunately, practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
1
44
0
Order By: Relevance
“…Existing post-BDA restoration studies primarily focus on biological changes at large restoration projects (Pollock et al, 2012;Bouwes et al, 2016;Silverman et al, 2018). A study of steelhead response post-restoration reported significant aggradation and groundwater rise proximal to BDAs, but the study design included over 100 structures, which is not typical of most BDA projects (Bouwes et al, 2016).…”
Section: Beaver Dam Abandonment and Subsequent Valley Bottom Changementioning
confidence: 99%
See 1 more Smart Citation
“…Existing post-BDA restoration studies primarily focus on biological changes at large restoration projects (Pollock et al, 2012;Bouwes et al, 2016;Silverman et al, 2018). A study of steelhead response post-restoration reported significant aggradation and groundwater rise proximal to BDAs, but the study design included over 100 structures, which is not typical of most BDA projects (Bouwes et al, 2016).…”
Section: Beaver Dam Abandonment and Subsequent Valley Bottom Changementioning
confidence: 99%
“…Studies from natural dams suggest that sedimentation might correlate to pool surface area and age, with larger and older BDA pools storing more sediment (Butler & Malanson, ; Naiman et al, ; Pollock, Heim, & Werner, ). Existing post‐BDA restoration studies primarily focus on biological changes at large restoration projects (Pollock et al, ; Bouwes et al, ; Silverman et al, ). A study of steelhead response post‐restoration reported significant aggradation and groundwater rise proximal to BDAs, but the study design included over 100 structures, which is not typical of most BDA projects (Bouwes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…midday photosynthetic capacity depression), however these conditions should at the same time increase evaporation rates from open water. A particularly interesting case is where beaver dams create ponds and wetlands in drier catchments, since a sustained water presence presents a local anomaly in water availability and may promote vegetation growth, and hence , to a far greater extent than would otherwise be possible (Fairfax and Small, 2018;Silverman et al, 2019). In semi-arid north-east Nevada, Fairfax and Small (2018) found a large increase in riparian vegetation abundance in beaver dammed river valleys, and estimated riparian to be 50 -150% higher than undammed areas.…”
Section: Figure_6: Changes In Open Water Area and Number Of Beaver Pomentioning
confidence: 99%
“…Combining beavers and the geomorphic basis of stage restoration efforts is particularly well suited to address the broader problem of historical channel incision, as the multithread channel system can reduce reach scale stream power and promote deposition (Pollock et al, 2014). In combination, these processes can lead to the lateral hydrological re-connection of the floodplain-channel system (Polvi and Wohl, 2013) and greatly reduces the sensitivity of riparian vegetation to rainfall variability in drier areas (Silverman et al, 2019). However, the continuing absence of beavers from many river systems targeted for restoration has led to the emergence of beaver dam analogue (BDA) construction as a complementary technique (Bouwes et al, 2016;Pollock et al, 2007;Pollock et al, 2014) that falls within the broader stage 0 approach.…”
Section: Beavers As Ecosystem Engineers and Their Role In River Restomentioning
confidence: 99%
“…Sustainability of mesic resources hinges on maintenance of ecological processes and associated land-use practices that foster drought resiliency (Gillson, Dawson, Jack, & McGeoch, 2013). Already being implemented are innovative techniques that restore degraded riparian systems by increasing mesic resistance to drought and elevating landscape productivity to benefit wildlife and ranching (Silverman et al, 2018). Another emerging solution is targeted removal of invasive conifer in high elevation sagebrush rangelands (Miller, Naugle, Maestas, Hagen, & Hall, 2017) known to increase snow retention and extend availability of soil water longer into the growing season (Kormos et al, 2017).…”
Section: Significant Conservation Emphasis Targets Publicly Managed Umentioning
confidence: 99%